Facility maintenance management system based on GIS and indoor map - Supattra Puttinaovarat; Suwat Jutapruet; Aekarat Saeliw; Siwipa Pruitikanee; Jinda Kongcharoen; Watchara Jiamsawat; Suchakree Limpasamanon (Institute of Advanced Engineering and Science, 2019)
This research presented a system development approach for facility maintenance management system based on GIS and indoor map in the form of web applications that can be used with all devices and no worries about time limitations. The capabilities of GIS, indoor map, and geospatial data visualization help speeding up facility maintenance management process and create benefits to all concerned parties, i.e., users can notify and follow the data of facility errors at the time; or officers in charge can operate quickly because they can access real-time data. Indoor map display makes it easier to access locations or places of damaged facilities. In addition, the data from the model system presented in this research can also be applied to planning and decision-making of executives.